Expression of liver alpha-amylase in obese mouse hepatocytes - Afsartala, Zohreh (Gastroenterol Hepatol Bed Bench, 2016)
AIM: The aim of this study is to demonstrate the relation between the expression of liver alpha-amylase and obesity. BACKGROUND: Alpha-amylase catalyses the hydrolysis of 1, 4-alpha-glucosidic linkages in polysaccharides and has three main subtypes, including: salivary, pancreatic, and hepatic. Hepatic alpha-amylase is involved in glycogen metabolism, and has a role in obesity and its management. In this study, we aimed to analyze the expression of liver alpha-amylase in overweight and obese mouse. MATERIAL AND METHODS: In this study, NMRI male mice were randomly divided into two groups. The sample group (obese) took a high-fat and carbohydrate diet, while the control group (normal) took a laboratory pellet chow for eight weeks. During this period, their weight was measured. After eight weeks, liver hepatocytes were isolated using an enzymatic digestion method. Immunocytochemistry (ICC) and flow cytometry analysis were performed to measure alpha amylase protein expression in mouse liver hepatocyte cells. RESULTS: A significant difference in the body weight was observed between the two groups (p<0.05). The qualitative protein expression of liver alpha-amylase was found to be higher in the obese group in both tests (immunocytochemistry and flow cytometry). Animals from the test group presented higher alpha-amylase expression, which suggests that this hepatic protein may constitute a potential indicator of susceptibility for fat tissue accumulation and obesity. The present data demonstrates an increased expression of liver amylase in obese mice. CONCLUSION: These results suggest that liver amylase secretion might be useful for predicting susceptibility to obesity induced by consumption of a high-fat and carbohydrate diet.